2023
DOI: 10.1002/med.21948
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of epithelial‐mesenchymal transition in cancer and its regulation by natural compounds

Abstract: Epithelial‐mesenchymal transition (EMT) is a complex process with a primordial role in cellular transformation whereby an epithelial cell transforms and acquires a mesenchymal phenotype. This transformation plays a pivotal role in tumor progression and self‐renewal, and exacerbates resistance to apoptosis and chemotherapy. EMT can be initiated and promoted by deregulated oncogenic signaling pathways, hypoxia, and cells in the tumor microenvironment, resulting in a loss‐of‐epithelial cell polarity, cell–cell ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(26 citation statements)
references
References 460 publications
0
16
0
Order By: Relevance
“…Various factors, including deregulated oncogenic signaling pathways, hypoxia, and cells present in the tumor microenvironment, can initiate and promote EMT. As a result, EMT leads to the loss of epithelial cell polarity and cell-cell adhesion, while promoting enhanced invasive and migratory properties (27). We can speculate that the increased EMT activity in the high-risk group promotes the progression of OC, thus making the prognosis of high-risk patients worse.…”
Section: Discussionmentioning
confidence: 99%
“…Various factors, including deregulated oncogenic signaling pathways, hypoxia, and cells present in the tumor microenvironment, can initiate and promote EMT. As a result, EMT leads to the loss of epithelial cell polarity and cell-cell adhesion, while promoting enhanced invasive and migratory properties (27). We can speculate that the increased EMT activity in the high-risk group promotes the progression of OC, thus making the prognosis of high-risk patients worse.…”
Section: Discussionmentioning
confidence: 99%
“…Various factors, including deregulated oncogenic signaling pathways, hypoxia, and cells present in TME, can initiate and promote EMT. As a result, EMT leads to the loss of epithelial cell polarity and cell-cell adhesion, while promoting enhanced invasive and migratory properties (30). We can speculate that the increased EMT activity in the high-risk group promotes the progression of OC, thus making the prognosis of high-risk patients worse.…”
Section: Discussionmentioning
confidence: 99%
“… 339 , 340 Over the years, it has been observed that EMT is reactivated during tumor progression, emerging as a pivotal mechanism for cancer cells to acquire malignant properties. 341 , 342 Various signaling pathways participate in the regulation of EMT, including the Notch signaling pathway (Fig. 3 ).…”
Section: The Mechanism Of Notch Signaling Patyway-mediated Tumorigene...mentioning
confidence: 99%